MODEL KOMUNIKASI PENYULUHAN NARKOBA OLEH YAYASAN BANTUAN HUKUM AMALBI (YBH AMALBI) DI KOTA DEPOK - Bagus Setiawan Muharom, (2022)
This research purposes is to see a process of counseling communicate that Legal Amalbi aid foundation in conducting drug counseling to society of Depok City Based on counseling communication model and theory of counseling communication. Method used is exploratory qualitative with case study type. This study uses data collection from multiple data sources in accordance with characteristics of case study research. Researcher uses technical analysis of matchmaking patterns according to Robert K. Yin, namely by analyzing empirical pattern obtained in the field with initial propositional pattern obtained during literature study. Then use withdrawal/verification with data triangulation. Final result of this study shows that counseling process carried out by YBH Amalbi is quite ideal because it takes place in two directions and is in accordance with the initial propositional pattern during the literature study. YBH Amalbi started counseling by inviting community discussions before giving the material to activate the community during counseling and create closeness with the community. So that drug counseling conducted by YBH Amalbi takes place in two-way communication and is quite interactive. Drug counseling conducted by YBH Amalbi also needs to improve the performance of the extension workers so that conditions do not happen again where feedback is hampered and use a speech tempo that is in accordance with what the community wants.